Homemade remedies causing contact dermatitis: case report on two patients with acne. - Leelavathi, M; Mazlin MB; Adawiyah J (Penerbit UKM, 2013)
Natural products are often perceived as safe due to the absence of artificial or chemical materials in its content. However, many are unaware that some of these compounds, albeit natural in existence, can cause harm. Cinnamon and lemon are two commonly used home remedies for acne. Both these naturally existing ingredients are capable of producing dermatitis upon contact with the human skin. The aim of this article is to create awareness among physicians that natural remedies are not free from harm hence, should look out for any possible untoward reactions that these products may cause. Physicians need to explore the possible use of homemade remedies to treat common or minor ailments during history taking as this information may not be given voluntarily. Early identification of the offending agent, adequate management and future avoidance could help prevent further episodes of contact dermatitis and its complications.